Research methods in intercultural communication : a practical guide - Hua, Zhu, 1970- (West Sussex : Wiley-Blackwell, 2016)
'The focus is on the process of interaction and what the participants achieve out of the experience in terms of new values, identities and practices'--
Keywords: Intercultural communication -- Research; Intercultural communication -- Methodology; LANGUAGE ARTS & DISCIPLINES / Linguistics / General